PENYELESAIAN SENGKETA TERHADAP PELAKU PEMBAKARAN TANAH ULAYAT OLEH FUNGSIONARIS ADAT DI DESA SALATIGA KECAMATAN MANDOR - NIM. A1012211077, FREDDY SAKSESA (Fakultas Hukum Universitas Tanjungpura, 2026)
Abstract This thesis discusses the resolution of disputes involving customary land burning by customary officials in Salatiga Village, Mandor District. Disputes over customary land burning are a significant issue within the Dayak Kanayatn indigenous community in Salatiga Village. This study aims to uncover the factors that contribute to disputes over customary land burning, the legal consequences (sanctions) for perpetrators of customary land burning, and the efforts made by customary officials to resolve disputes concerning customary land burning within the Dayak Kanayatn indigenous community. The research method used is empirical juridical research with a qualitative descriptive approach, combining primary data obtained through direct interviews with customary officials, perpetrators of burning, and community members as witnesses, along with secondary data in the form of legal materials and literature relevant to the research topic. The results indicate that customary officials play a crucial role in resolving customary land burning disputes. In the Dayak Kanayatn customary legal system, customary officials serve as supreme leaders, tasked with upholding justice, maintaining balance, and protecting the rights of indigenous communities. Negligence, unclear land boundaries, and a lack of awareness of customary law contribute to the burning of customary land. Based on customary deliberations led by customary officials, those who burn customary land are subject to the customary sanction